POLA KOMUNIKASI INTERPERSONAL PADA KOMUNITAS SAVE STREET CHILD SIDOARJO DALAM BIDANG PENDIDIKAN - Aji Nugroho, Muhammad Faizal; Setyarahajoe, Ratna; Fadeli, Muhammad (Triwikrama: Jurnal Ilmu Sosial, 2025)
Education serves as the foundation of every child’s life, including those who are often disadvantaged by the formal education system. Not all children have equal opportunities to access proper education, particularly street children or those living in marginalized conditions. For these children, the Save Street Child Sidoarjo community provides an alternative space for learning that is more flexible, inclusive, and oriented toward their specific needs. This study aims to examine the patterns of interpersonal communication used by volunteers and caregivers in accompanying the learning process of “anak merdeka” within the community. The focus of this research is not only on how messages are delivered, but also on how interpersonal relationships are built through empathetic, open, and participatory communication. Using a qualitative descriptive method, data were collected through direct observation and in-depth interviews with volunteers and children involved in the learning activities. The results show that personal, empathetic, and participatory communication patterns create an inclusive and independent learning environment. Furthermore, effective communication has been proven to enhance learning motivation, self-confidence, and active participation among the children.